End-system traffic control for guaranteed video quality of experience - Peng, Shuai. (2010)
With the rapid rising of real time applications, deterministic Quality of Service provisioning has become more important each day as these applications use the Internet to carry their traffic. Many mechanisms such as Differentiated Service and MultiServ have been proposed to provide QoS guarantees but the scalability of these mechanisms is still an open issue. In this report, detailed information about a novel Scalable MultiServ mechanism will be presented. This mechanism employs a Distributed-FDPS algorithm that pushes computation complexity to end-systems, and removes flow state information from routers in the network thereby making the mechanism scalable. The behaviors of video traffic have been analyzed for traffic characterization needed for computer simulations. Computer simulations using NS-2 simulator will also be implemented to verify the effectiveness of the new mechanism. Implementation procedures of the simulation will be described in this report and the results of several test cases will be analyzed.